Spatially resolved characterization of a dc magnetron plasma using optical emission spectroscopy. (13th September 2018) - Ries, Stefan; Bibinov, Nikita; Rudolph, Marcel; Schulze, Julian; Mráz, Stanislav; Schneider, Jochen M; Awakowicz, Peter
Abstract: In this work, a reactive argon−nitrogen [ Ar/N 2 ( 10 / 1 ) ] dc magnetron plasma for sputtering of a chromium (Cr) target is characterized with high spatial resolution by optical emission spectroscopy (OES) using molecular nitrogen emission bands at 0.5 Pa and 100 W. Beside the global gas temperature T g, the electron temperature T e, electron density n e, and the steady-state Cr density n Cr are also determined spatially resolved using a movable OES setup inside the chamber and Abel inversion. n e and T e are found to be consistent with the values measured by a Langmuir probe (LP) within the non-magnetized region along the magnetron axis in a pure Ar plasma for the same process parameters. Finally, a nitrogen content c N of 4% in the target surface is found for the reactive plasma by matching the mean steady-state chromium density n ̄ Cr measured by OES and calculated from TRIDYN simulations.